Towards mental training for elite judo athletes - Gabriel, C. A. (The Arts and Sciences of Judo, 2022)
This research note aims to present the potential benefits of mental training for elite judo athletes and advocates the implementation of mental training policies and programmes within judo organisations as a key organisational factor that can be controlled for the benefit of health and performance of elite judo athletes and in favour of the international sporting success of nations. Five key benefits are presented, demonstrating the challenges that elite athletes face and then how mental training can contribute to solving these challenges based on existing studies and theories. These five benefits can inform the decision-making of managers of judo organisations and the formulation of management policies associated with mental training. In addition, the benefits presented can also be considered as testable hypotheses for future research. In the context of elite judo, mental training has the potential to (1) increase athletes' control over mental health; (2) teach athletes to self-generate positive emotions, thereby broadening their repertoires of thoughts-actions to task-oriented coping strategies, building resilience, thus leading athletes to an upward spiral dynamic characterised by the optimisation of health, well-being and performance; (3) undo the effects of negative emotions; (4) mitigate the debilitating physiological effects of critical moments of competition; (5) reduce perceived exertion and increase resilience to mental fatigue in training and competitions. Finally, the research note concludes by calling managers of judo organisations and coaches to action, mainly encouraging the implementation of mental training policies and programmes for the benefit of judo athletes' development.